Digital Resources and Digital Competence: A Cross-Sectional Survey of University Students of the Childhood Education Degree of the University of Jaén - María del Carmen Martínez-Serrano; María Teresa Ocaña-Moral; Eufrasio Pérez-Navío (MDPI AG, 2021)
This work is part of a broader investigation whose main objective is to determine the domain and preferences of the students of the Childhood Education Degree of the University of Jaén regarding digital competence. The research was focused on the "use of digital resources" dimension and was developed under a quantitative and descriptive methodology, of basic type and non-experimental cross-sectional design. We worked with a sample of 135 students from the four courses of the Childhood Education Degree of the University of Jaén, who answered a developed questionnaire voluntarily and anonymously. Data collection was carried out using a virtual questionnaire on the Google Form platform. In addition, the measurement instrument was considered valid and reliable, having obtained a Cronbach's alpha coefficient (α) of 0.925 and a Kaiser-Meyer-Olkin sampling adequacy index (KMO) of 7.741. The results show that there are no significant differences based on the independent variables studied among most of the analyzed items. The use of ICT is beneficial for students' participation in research.